Variable selection for longitudinal survey data - Dumitrescu, Laura; Qian, Wei; Rao, JNK (Journal of Statistical Research, 2021)
In this article we propose a new variable selection method for analyzing data collected from longitudinal sample surveys. The procedure is based on the survey-weighted quadratic inference function, which was recently introduced as an alternative to the survey-weighted generalized estimating function. Under the joint model-design framework, we introduce the penalized survey-weighted quadratic inference estimator and obtain sufficient conditions for the existence, weak consistency, sparsity and asymptotic normality. To illustrate the finite sample performance of the model selection procedure, we include a limited simulation study. Journal of Statistical Research 2021, Vol. 55, No. 1, pp. 21-41